Heterotypic Infection and Spread of Rhinovirus A, B, and C among Childcare Attendees. (19th April 2018) - Martin, Emily T; Kuypers, Jane; Chu, Helen Y; Foote, Sydney; Hashikawa, Andrew; Fairchok, Mary P; Englund, Janet A
Abstract : This longitudinal study of HRV detection in childcare attendees demonstrates sequence-confirmed clusters of rhinovirus within the context of continuous heterotypic circulation of multiple strains in both symptomatic and asymptomatic children. Abstract: Background: Despite the frequency of human rhinovirus (HRV), data describing the molecular epidemiology of HRV in the community are limited. Childcare centers are optimal settings to characterize heterotypic HRV cocirculation. Methods: HRV specimens were prospectively obtained from a cohort of childcare attendees at enrollment and weekly during respiratory illness. The 5′ noncoding region sequences were used to determine HRV species (A, B, C) and genotypes. Results: Among 225 children followed, sequence data were available for 92 HRV infections: HRV-A (n = 80; 59%) was most common, followed by HRV-C (n = 52, 39%), and HRV-B (n = 3, 2%). Forty-one genotypes were identified and cocirculation was common. Frequent spread between classrooms occurred with 2 HRV-A genotypes. Repeated detections within single illnesses were a combination of persistent (n = 7) and distinct (n = 7) genotypes. Prevalence of HRV among asymptomatic children was 41%. HRV-C was clinically similar to HRV-A and HRV-B. Conclusions: HRV epidemiology in childcare consists of heterotypic cocirculation of genotypes with periodic spread within and among classrooms. Based on our finding of multiple genotypes evident during the course of single illnesses, the use of sequence-based HRV type determination is critical in longitudinal studies of HRV epidemiology and transmission.